Adaptive second-order fast nonsingular terminal sliding mode control for robotic manipulators. (July 2019) - Yi, Shanchao; Zhai, Junyong
Abstract: This paper presents an adaptive chattering-free sliding mode controller for trajectory tracking of robotic manipulators in the presence of external disturbances and inertia uncertainties. To achieve fast convergence and desirable tracking precision, a second-order fast nonsingular terminal sliding mode (SOFNTSM) controller is designed to guarantee system performance and robust stability. Chattering is eliminated using continuous control law due to high-frequency switching terms contained in the first derivative of actual control signals. Meanwhile, uncertainties are compensated by introducing the adaptive technique, whose prior knowledge about upper bound is not required. Finally, simulation results validate the effectiveness of the proposed control scheme. Highlights: A SOFNTSM controller is designed to ensure fast convergence and trajectory tracking. Actual control law after integral is continuous and thus system is chattering-free. Without prior knowledge of uncertainties, adaptive laws are designed to estimate them.